Utilization and Perception of Telemedicine in Indonesia: Healthcare Providers Point of View - Silvalena Silvalena; Rizma Adlia Syakurah (Jurnal Kesehatan Masyarakat Andalas, 2022)
The popularity of Telemedicine nowadays has started to bloom and increasingly becoming accepted practice in Indonesia. However, it is still vague whether the available telemedicine platforms in Indonesia have already met the standards and needs of the users. This study aimed to evaluate the utilization and perception of telemedicine users from the perspective of healthcare providers. One hundred and eighteen responses were gathered to see healthcare providers' point of view on the telemedicine platform they used using a social-media broadcasted questionnaire. This questionnaire was adapted from the mHealth Application Usability Questionnaire (MAUQ) to see healthcare providers' points of view on the telemedicine platform they used. Data obtained from 16th - 29th June 2020 were analyzed descriptively then presented in a distribution table. Four telemedicine platforms mainly used were Alodokter, Halodoc, Mobile JKN, and Hospital-linked Telemedicine. Three-forth of respondents stated that they used the telemedicine platform due to the flexible working hours (75.4%), as an alternative during the pandemic and easy to use (71.2%), widespread in the society (50.8%), and most healthcare services have consultation sessions (93.2%). The majority of respondents prioritized doctor-patient communication during practice (89.0%). SehatPedia had the highest average score among platforms users. Majority of healthcare providers feel the benefits of using telemedicine. The quality of healthcare service served by healthcare providers does not diminish compared to in-person healthcare service, and that Telemedicine should further be developed.